Young ecopreneur training to enhance entrepreneurial competencies in UII High School: Pelatihan Young Ecopreneur untuk Mendukung Keunggulan Kewirausahaan di SMA UII - Kuntari, Titik; Roostika, Rr Ratna; Wijayanti, Punik Mumpuni; Utami, Utami; Kusumaningputri, Dyah Sekar Ayu; Wijayanto, Muhammadiena Ramadhannisa (Universitas Lancang Kuning, 2025)
Organic fruit and vegetable waste is among the garbage that cannot be appropriately managed. Waste can be converted into eco enzymes, which are beneficial and economically valuable. UII High School, as the environmental rescue school title winner, has three benefits, one of which is entrepreneurship. Community service activities include offering knowledge and training on how to make ecoenzymes, eco enzyme derivative products, and digital marketing. The events, with the participation and cooperation of students, instructors, and parents, are expected to help young entrepreneurs realize their dreams of being creative, and innovative, producing environmentally friendly products, and having strong digital marketing skills. The training comprised teachers and school committees, with the goal that this program might be further developed